2019
DOI: 10.1186/s12873-019-0235-4
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory compromise in children presenting to an urban emergency department of a tertiary hospital in Tanzania: a descriptive cohort study

Abstract: Background Respiratory compromise is the leading cause of cardiac arrest and death among paediatric patients. Emergency medicine is a new field in low-income countries (LICs); the presentation, treatment and outcomes of paediatric patients with respiratory compromise is not well studied. We describe the clinical epidemiology, management and outcomes of paediatric patients with respiratory compromise presenting to the first full-capacity Emergency Department in Tanzania. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Therefore, intubation is done at a very late stage in their stay at the EMD and thus carries a high risk of cardiac arrest. Similar to other studies, intubation was found to be independently associated with cardiac arrest [ 9 , 13 ].…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, intubation is done at a very late stage in their stay at the EMD and thus carries a high risk of cardiac arrest. Similar to other studies, intubation was found to be independently associated with cardiac arrest [ 9 , 13 ].…”
Section: Discussionsupporting
confidence: 88%
“…Reports from LMIC tend to come from single institutions and reflect their level of care and admission policies. In an emergency department of a Tanzanian teaching hospital, 18/165 (11%) infants <1 year of age required CPR [5]. A report from South India states that 27% (20/75) of children arriving at the hospital with agonal breathing received CPR in the emergency department [6].…”
Section: Epidemiologymentioning
confidence: 99%
“…The 53 studies containing ‘AFEM-CC quality indicators near match’ evidence were split between two groups of publications. The first group included 38 publications, which were identified as containing only ‘AFEM-CC quality indicators near match’ data 57–94. The second group included 15 publications, which were cited above as containing ‘AFEM-CC quality indicators exact match’ data, but which contained additional ‘AFEM-CC quality indicators near match’ data 22 25 26 28 29 31 33 34 39 41 45 46 54–56.…”
Section: Resultsmentioning
confidence: 99%